Helium Ion Microscopy: Helium Ion Microscopy Visualizes Lipid Nanodomains in Mammalian Cells (Small 43/2015). Issue 43 (November 2015) - Schürmann, Matthias; Frese, Natalie; Beyer, André; Heimann, Peter; Widera, Darius; Mönkemöller, Viola; Huser, Thomas; Kaltschmidt, Barbara; Kaltschmidt, Christian; Gölzhäuser, Armin
Abstract : On page 5781, B. Kaltschmidt, C. Kaltschmidt, A. Gölzhäuser, and co‐workers show how helium ion microscopy is capable of imaging biological specimens without any conductive coating, and it allows the identification of nanodomains in the ultrastructure of membranes with 1.5 nm resolution. The image here shows two mouse neurons. One neuron is imaged with an optical microscope, the other neuron is imaged with the helium ion microscope. The helium ion microscope image includes a high‐resolution inset, which depicts membrane nanodomains.